Produção textual de surdos sinalizantes de LIBRAS, em português escrito, a partir da modelização didática de gêneros textuais: a escrita de surdos em foco - Oliveira, José Carlos de (2022)
The practice of “textual production” language helps subjects to play their social role, because the subject who writes well can act in different social practices, can argue, positioning himself in defense of a point of view; In short, you can act/interact in the world. In our research, for the development of some of these practices, we plan to work with textual genres, from the production of genres report of lived experience and resume of thirteen deaf participants signaling, which allowed us to conduct a case study during the elaboration of this doctoral thesis. The general objective of the study was to investigate and analyze the development of language skills mobilized in the production of genres report of experienced and resume of deaf subjects signaling Brazilian sign language - Libras as the first language, in their textual productions in Portuguese written, by A means of didactic sequences elaborated for a Portuguese course taught with second -language teaching methodology for the deaf. As specific objectives, we have: (a) to verify that the work developed with didactic sequences, anchored in a second language teaching proposal, contributes to the textual production of the participants; (b) to analyze the observable properties (characteristics) expressed in textual productions in genres report of experience lived and summary to build their representation through language action; (c) to verify that the language skills mobilized by participants in initial production in genres report of experience lived and summary present differences in the final productions of texts in these genres. As a theoretical-methodological contribution, we support research in the textbook model (DOLZ;SCHNEUWLY, 2004b), in the didactic sequence (DOLZ; NOVERRAZ;SCHNEUWLY, 2004), the second-language teaching methodology (Krashen, 1982) and the model Analysis of Socio -Cursive Interactionism (BRONCKART, 1997, 1999). The research is also anchored regarding the genre report of experience lived, in studies by Köche et al (2012) and, for the genre Abstract, Medeiros (2009), Machado; Lousada; Abreu-Tardelli (2004) and Cotentin-Rey (1995). For the analysis of pounds texts (used only for the elaboration of the teaching model of gender), in the two chosen genres, following the linguistic characteristics of Libras, according to pictures and Karnopp (2004). The analysis of the data generated through the initial production and the final production of each research participant points out that the work developed in the research contributes to the development of the language capacities necessary for the production of genres and also indicates the need for text production In Libras, in the different textual genres, whether those in everyday life or the students, especially the university/academic sphere, to support the teaching of textual genres in written Portuguese. Thus, our research contributes to deaf studies in the context of bilingual education, as it brings contributions to different research groups, such as the group analysis of language, educational work and their relationships - learning, textual genres and teaching, as well as for Curriculum proposal for the teaching of Portuguese written for the deaf and for the training of teachers in undergraduate courses with specific end in the area of Portuguese teaching written by and for the deaf, without neglecting all those interested in the theme.